When the going gets tough, leaders use metaphors and storytelling: A qualitative and quantitative study on communication in the context of COVID-19 and Ukraine crises - Katerina Gkalitsiou; Dimosthenis Kotsopoulos (Administrative Sciences, 2023)
Metaphors and storytelling are important communication tools that play a significant role in leadership and organizational life. Leaders have used metaphors and storytelling to enhance their written and verbal communication from ancient times, since Aristotle, to the modern age. In the present research, we focus on the use of storytelling and metaphors by leaders in times of crisis. We perform a qualitative analysis of the public statements and addresses of the leaders of two different countries in the context of recent worldwide crises: The prime minister of Greece during the COVID-19 health crisis and the president of Ukraine during the outbreak of the conflict with Russia in 2022. Based on existing evidence, their effectiveness in convincing their subordinates and conveying their intended meaning either nationally or internationally during the aforementioned crises has been widely recognized. Our analysis reveals that both leaders have consistently utilized metaphors and storytelling in their efforts to be more convincing and empowering. We also find that the higher the intensity of the crisis, the more pronounced the use of metaphors and stories. We accordingly provide an analysis of the types and frequency of use of the aforementioned communication tools. Reflecting on our findings, we provide specific insight for practice by leaders, discuss theoretical implications, and suggest directions for future research.
Keywords: 350; communication; COVID-19; crisis; Greece; information strategy; leadership; metaphors; politics; stories; storytelling; taxonomy; Ukraine